Petroleum reservoir simulation - Islam, M. Rafiqul; Abou-Kassem, Jamal H. (Jamal Hussein); Farouq-Ali, S. M. (Gulf Professional Publishing, 2019)
Petroleum Reservoir Simulation, Second Edition, introduces this novel engineering approach for petroleum reservoir modeling and operations simulations. Updated with new exercises, a new glossary and a new chapter on how to create the data to run a simulation, this comprehensive reference presents step-by-step numerical procedures in an easy to understand format. Packed with practical examples and guidelines, this updated edition continues to deliver an essential tool for all petroleum and reservoir engineers.